The Impact of the Covid-19 Pandemic on Eating Behavior among Adults Poles - Agnieszka Panasiuk; Kamil K. Hozyasz (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Due to the outbreak of coronavirus disease (COVID-19), many restrictions and temporary lockdown were carried out. As a result, previous lifestyle, including diet, were disrupted.Objectives: The aim of this review was to assess changes in eating behavior during the COVID-19 compared to the period before pandemic in Poland. Methods: In the review involved original studies concerning adults Poles (aged ≥ 18), including changes in their eating behavior.Results: The COVID-19 pandemic and the social isolation periods had ambiguous influence on diet in Poland. The changes were dependent on many factors e.g. age, sex, education, occupation, or body weight. In general, regular diet pattern was followed. In case of changes, positive and negative eating habits were observed. Improper eating behavior such as the increase of total food and junk food intake was noticed, however improvement of the diet also was observed. Consumption of healthy food, such as vegetables and fruit went up. The significant increase of home cooking also was noticed.Conclusions: The present review indicates the need for future strategies to assess nutrition in cases of alarming situations. Promoting healthy eating behavior appears to be essential, especially during the pandemic.